PENGARUH PEMBELAJARAN EKONOMI SYARIAH TERHADAP MINAT MENABUNG DI BANK SYARIAH (STUDI KASUS MAHASISWA FEBI UIN RADEN FATAH PALEMBANG) - Sari, Vera Aprillia Sari; Putri Nur'Aini, Dwi Putri Nur'Aini; Kurniadi Sallam , Muhammad Al Fajri Kurniadi Sallam (Asyafina Journal: Jurnal Akademi Pesantren, 2023)
This studi aims to determine wheter or not there is an influence of Islamic Economic learning on student’s interest in saving at Islamic banks, especially FEBI students at UIN Raden Fatah Palembang. The method used in this study is a quantitative method with the analysis used is a simple linear regression analysis technique. The primary data source in this study was obtained through distributing questionnaires online using googleform with the likert scale as the instrument. The result showed that learning Islamic Economics had a positive effect on the intention to save at Islamic Banks, especially for FEBI students at UIN Raden Fatah Palembang with the ANOVA table, the SIG. 0,000 which means < significant level (0,05) or Ho is rejected where the linear regression equation Y = 4,628 + 0,781X is significant and has a linear pattern, which means that if student’s understanding of Islamic banking in Islamic Economics learning increases, the interest in saving in Islamic banks increases by 78%. The better the understanding of students in learining Islamic Economic, the greater the student”s interest in saving at Islamic BanksThe abstract should be clear, concise, and descriptive. This abstract should provide a brief introduction to the problem, objective of the paper, followed by a statement regarding the methodology and a brief summary of results. The abstract should end with a comment on the significance of the results or a brief conclusion. Abstracts are written in 10pt Times New Roman, preferably not more than 200 words.